Life Disruptions, Symptoms Suggestive of Endometriosis, and Anticipated Stigma Among College Students in the United States - Jhumka Gupta; Lauren Cardoso; Samantha Kanselaar; Anna M. Scolese; Alzahra Hamidaddin; Anna Z. Pollack; Valerie A. Earnshaw (Mary Ann Liebert, 2021)
Background: Endometriosis is a chronic gynecological condition impacting 1 in 10 women of reproductive age. Research with adult women documents high levels of disruptions in academic, professional, family, and social lives due to pain. Less research has been conducted with college-aged populations. Although stigma has been noted as a key factor in contributing to diagnostic delay, little research has focused on examining stigma, endometriosis symptoms, and disruptions. This study aims at documenting the frequency of social, academic, and work disruptions experienced by college-aged women due to symptoms suggestive of endometriosis and at examining the relationship between disruptions and anticipated stigma. Methods: An online survey was conducted in April 2019 among a nationally drawn sample (N?=?468) of undergraduate women to assess symptoms suggestive of endometriosis, disruptions to daily life, and stigma experiences. Results: High levels of life disruptions due to symptoms suggestive of endometriosis were documented (88% any disruption, 82.7% social, 58.8% academic, and 34.4% work). Adjusted analysis (accounting for demographics and symptoms) showed that any disruptions, social disruptions, academic disruptions, or work disruptions were significantly associated with a higher mean anticipated stigma score (??=?0.37, 95% confidence interval [CI]: 0.15?0.59; ??=?0.32, 95% CI: 0.13?0.51; ??=?0.32, 95% CI: 0.17?0.46; ??=?0.55, 95% CI: 0.23?0.54; respectively). Conclusions: Many young women experience disruptions that affect their academic, work, and social lives. These disruptions due to symptoms suggestive of endometriosis also impact stigma experiences. More interventions tailored to address stigma and minimize disruptions are needed in public health.